MICROALGAE COMMUNITY AS AQUATIC QUALITY BIOINDICATOR IN PENITI ESTUARY WEST KALIMANTAN - Apriansyah Apriansyah; Ikha Safitri; Risko Risko; Afdal Afdal; Sulastri Arsad (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2021)
Estuaries are biogeochemical hot spots; they receive large inputs of nutrients from land and oceans to support high primary productivity rates. Estuaries also as a place for waste disposal allowing the accumulation that endangers the environment and organisms. Water quality assessment can be done by analyzing physical, chemical, and biological characteristics using microalgae. This study aimed to analyze the microalgae community as aquatic environment bioindicator. Survey method was used and sampling location was in four different sites of Peniti Estuary by purposive sampling. Identification of microalgae, density, biological indexes, and water quality measurements was taken in this research. The result showed microalgae community consists of 68 genera and Euglenophyceae was a component of microalgae with the highest percentage of abundance (60.93%). The most commonly found genera were Trachelomonas, Phacus, Lepocinclis, and Sphaerellopsis. The abundance of microalga was ranging from 0.5-2141.5 ind/L. Biological indexes indicate that Peniti estuary environment was belonging to moderately polluted and water eutrophication. The abundance of microalgae was influenced by physico-chemical factors such as temperature, current, nitrate and phosphate content.